Low Molecular Weight Hyaluronic Acid Effect on Dental Pulp Stem Cells In Vitro - Schmidt, Jan; Pilbauerova, Nela; Soukup, Tomas; Suchankova-Kleplova, Tereza; Suchanek, Jakub (Biomolecules, 2020)
Hyaluronic acid (HA) and dental pulp stem cells (DPSCs) are attractive research topics, and their combined use in the field of tissue engineering seems to be very promising. HA is a natural extracellular biopolymer found in various tissues, including dental pulp, and due to its biocompatibility and biodegradability, it is also a suitable scaffold material. However, low molecular weight (LMW) fragments, produced by enzymatic cleavage of HA, have different bioactive properties to high molecular weight (HMW) HA. Thus, the impact of HA must be assessed separately for each molecular weight fraction. In this study, we present the effect of three LMW-HA fragments (800, 1600, and 15,000 Da) on DPSCs in vitro. Discrete biological parameters such as DPSC viability, morphology, and cell surface marker expression were determined. Following treatment with LMW-HA, DPSCs initially presented with an acute reduction in proliferation (p < 0.0016) and soon recovered in subsequent passages. They displayed significant size reduction (p = 0.0078, p = 0.0019, p = 0.0098) while maintaining high expression of DPSC markers (CD29, CD44, CD73, CD90). However, in contrast to controls, a significant phenotypic shift (p < 0.05; CD29, CD34, CD90, CD106, CD117, CD146, CD166) of surface markers was observed. These findings provide a basis for further detailed investigations and present a strong argument for the importance of HA scaffold degradation kinetics analysis.
Keywords: zubní dřeň; Hyaluronic Acid; Humans; proliferace buněk; Cell Differentiation; Dental Pulp; lidé; buněčná diferenciace; tkáňové inženýrství; Cells, Cultured; molekulová hmotnost; Molecular Weight; Stem Cells; Tissue Engineering; kmenové buňky; kyselina hyaluronová; kultivované buňky; Cell Proliferation